Some Legal Problems Encountered In The Acquisition Of A New Mineral Property - R. E. Driscoll (Society for Mining, Metallurgy & Exploration, 1958)
The exploration, geologist of necessity has to have a wide working knowledge of many specialties other than hiw own, First he has to use his own technical background to find a deposit,, of a mineral that is of interest, Once found, his problems are Just beginning, He then has to assume the role of an economist, an accountant, a mining engineer, a chemist, a metallurgist,, a salesman and what-have you, In the economic field, he must determine the marketability of either the ore or the refined mineral. He must gauge the supply and demand for the particular mineral he is interested in and make his best guess as to ultimate cash flow from a deposit over the estimated life of said deposit, He must then assume the role of a mining man and estimate cost of recovery, including an, evaluation of the most economic mining method, cost of supplies and labor, and again estimate a net cash flow. He must then determine amenability of ore to economic metallurgical methods, he must determine the legal status of the property involved and, after analysis of the specific situation, determine the best approach to a deal, After all of this he must sell it to the people who will put up the money and then put his deal together and sell it to the people who own the minerals, if that be necessary. Then he has to sit back, with crossed fingers and crossed legs wondering for some months, and in many cases even years, whether or not he is right. The expenditures required to open up a mine in this day of wild inflation are such that he has to be right, and the responsibilities are awesome.